Answer: 12
Step-by-step explanation:
Answer:
Alright well the simplified system is arbitrary solution of the original system of equation
a1 = - 15
an = - 15/4 Hope this helps have nice day :)
Step-by-step explanation:
I would first make it 5+-2x and so then you would have I5+-2xI * IxI and then you have I5+ (-2*-4)I*I-4I then you have I5+8I*4 then you would have 13*4 and then your answer is 52 :)
Answer:
Simplifying
x = 11
Step-by-step explanation:
Simplifying
6x + -27 = 39
Reorder the terms:
-27 + 6x = 39
Solving
-27 + 6x = 39
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '27' to each side of the equation.
-27 + 27 + 6x = 39 + 27
Combine like terms: -27 + 27 = 0
0 + 6x = 39 + 27
6x = 39 + 27
Combine like terms: 39 + 27 = 66
6x = 66
Divide each side by '6'.
x = 11
Simplifying
x = 11
Answer:
(5,2)
Step-by-step explanation:
Answer (5,2)
N(2)
W E(5)
S